The role of economic complexity in shaping the energy-growth nexus: Evidence from cross-country panel data - Al-Silefanee, Rebean (Center of Biomass & Renewable Energy (CBIORE), 2024)
The study investigated the interplay between energy consumption (EN), economic growth (EG), and economic complexity across 59 countries from 2000 to 2018. Employing panel data methods, the research examined various models to estimate long-term effects while addressing unobserved heterogeneity and potential biases. Results indicate significant relationships between EG, EN, and economic complexity. Notably, the economic complexity index (ECI) displayed a positive effect on economic development, while trade openness and foreign direct investment showed varying impacts. The study identified a positive association between EG and EN, suggesting that increased energy consumption accompanies economic growth. However, a higher capital-to-labor ratio was associated with lower EN, indicating a substitution effect. Of particular note is the significant positive impact of the interaction between ECI and EN on GDP across various models. In the Country Fixed Effects Model, a one-unit increase in the interaction correlated with a 0.026 unit increase in GDP (p < 0.001). Similarly, significant positive relationships were observed in the Panel EGLS and FMOLS models, with coefficients of 0.055 and 0.031, respectively (p < 0.001 and p = 0.011). Conversely, all models consistently demonstrated a negative relationship between economic complexity and GDP, with coefficients ranging from -0.062 to -0.089 (p < 0.001). These findings underscore the importance of considering economic complexity and energy consumption in policy interventions aimed at promoting sustainable economic growth. Policymakers are encouraged to adopt comprehensive approaches that account for the complex interplay of various factors influencing economic development and energy consumption to formulate effective strategies.